Performance Assessment of Open-Loop and Closed-Loop Generation Rate Constraint Models for Optimal LFC of the Three-Area Reheat Thermal System - Sai Kalyan, CH. Naga; Goud, B. Srikanth; Reddy, Ch. Rami; Kumar, M. Kiran; Bajaj, Mohit; El-Naggar, Mohamed F.; Kamel, Salah (Frontiers in Energy Research, 2022)
In this article, a novel investigation is performed to showcase the best suitable structure of the generation rate constraint (GRC) for the three-area reheat thermal power system (RTPS) to obtain load frequency control (LFC) optimally. For investigation purposes, two GRC models which are widely implemented in the literature without providing any discussion of their selection and suitability are confiscated in this article. The two GRC structures deliberated in the present article are termed as open-loop and closed-loop models. The performance of the three-area reheat thermal unit is examined with these two GRC structures for a perturbation of 10% step load (10% SLP) on area-1. An investigation is performed under the governance of a three-degree-of-freedom PID (3DOFPID) controller, fine-tuned using a water cycle algorithm (WCA) subjected to index integral square error (ISE) minimization. However, the efficacy of the proposed WCA-tuned 3DOFPID controller is revealed with other control approaches available in the literature upon implementation of a widely accepted model of a two-area hydrothermal system. Finally, the simulation results and sensitivity analysis showed the suitable GRC structure for a three-area reheat thermal unit to obtain LFC optimally with high performance.